Technology Based Public Service Innovation in The Digital Era: A Qualitative Study at The Ministry of Population and Family Development, East Jakarta, Dki Jakarta Province - Nurhani, Siti; Handayani, Ninik Sidik; Hayeemasae, Muhammadsaddam; Noviawati, Yuli (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to evaluate the effectiveness of public service delivery in remote areas by focusing on the implementation of Minimum Service Standards (SPM) in Agats District, Asmat Regency, South Papua. As a region with challenging geographical characteristics and limited infrastructure, Agats District faces various obstacles in providing quality and equitable public services. This research employs a descriptive qualitative approach, utilizing data collection techniques such as interviews, observations, and document studies. The findings indicate that the implementation of SPM in Agats District has not been fully optimal. The main obstacles include a lack of personnel and inadequate staff competencies, limited facilities and infrastructure, and difficult inter-village accessibility. Nevertheless, there have been efforts by the local government to improve service quality, including staff training programs, locally-based service approaches, and cross-sectoral synergy. This study recommends the need for enhancing human resource capacity, improving basic infrastructure, and strengthening the commitment of local governments in fulfilling SPM in remote areas.